PENGARUH MODIFIKASI LAUK NABATI TERHADAP CITA RASA DAN DAYA TERIMA MENU MAKAN PAGI PASIEN RAWAT INAP - Rosida, Oktania; Akhriani, Mayesti; Junita, Dera Elva; Wahyudi, Dian Arif (JOURNAL HEALTH AND NUTRITIONS, 2025)
The acceptability of hospital food is reflected by the amount of food left over. High levels of leftover food result inadequate nutrition for patients and economy aspect indicate wasted costs, which makes the food budget inefficient and ineffective. The study was aimed to determine the effect of plant-based dish modification on the taste and acceptability of the breakfast menu for Class III inpatient patients. The study was quantitative that used a quasi-experimental design with a static group comparison design, conducted in October 2024, at Batin Mangunang Regional General Hospital. The sample consisted of all Class III soft food diet patients with total 30 respondents using purposive sampling as the sampling technique. The total population was 30 patients. Bivariate analysis in this study used the Wilcoxon test. Data collected was using the instrument questionnaire. The results of the study showed that there was an effect of modifying the plant-based dish (tofu) on acceptability and preference levels for appearance (p-value 0.000), color (p-value 0.001), shape (p-value 0.001), portion (p-value 0.001), presentation (p-value 0.001), taste (p-value 0.001), aroma (p-value 0.001), cooking level (p-value 0.001), seasoning (p-value 0.001), and temperature (p-value 0.001). Based on the results of the analysis, it was concluded that there was a relationship between modifications of the vegetable side dish menu of tofu and the acceptability which could affect the patient's food intake. Jumlah makanan yang tersisa sangat sedikit, menunjukkan daya terima makanan pasien rumah sakit. Tingkat sisa makanan yang tinggi dapat mengurangi kebutuhan gizi pasien dan secara ekonomis dapat menyebabkan anggaran makanan kurang efisien dan efektif. Tujuan penelitian untuk mengetahui bagaimana perubahan lauk nabati berdampak pada cita rasa dan daya terima menu makan pagi pasien rawat inap kelas III. Penelitian kuantitatif ini menggunakan desain quasi eksperimen dengan rancangan perbandingan grup statis, dan telah dilakukan di RSUD Batin Mangunang pada bulan Oktober 2024. Pada penelitian ini, subjek yang digunakan ialah seluruh pasien diet makanan lunak kelas III, yang berjumlah 30 responden. Teknik pengambilan sampel adalah purposive sampling dengan total populasi 30 pasien. Penelitian ini menggunakan uji Wilcoxon untuk analisis bivariat. Pengumpulan data menggunakan instrumen kuesioner. Hasil penelitian menyatakan bahwa terdapat pengaruh modifikasi lauk nabati tahu terhadap daya terima dan tingkat kesukaan penampilan (p-value 0,000), warna (p-value 0,000), bentuk (p-value 0,000), porsi (p-value 0,000), penyajian (p-value 0,000), rasa (p-value 0,000), aroma (p-value 0,000), tingkat kematangan (p-value 0,000), bumbu (p-value 0,000), dan suhu (p-value 0,000). Berdasarkan hasil analisis disimpulkan terdapat hubungan diantara modifikasi menu lauk nabati tahu dengan daya terima yang dapat memengaruhi asupan makan pasien.